Effect of various fibre loading of pineapple leaf fibre on polylactic acid composites filament - Muhammad, Noryani; Yusoff Zalman, Muhammad Naim; Mohamad, Nurul Nadia; Abdul Mutalib, Muhammad Alif Zuhair; Mohammad Taha, Mastura (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
Recently, natural fibres have been widely utilized because they are firmer and have higher strength comparable to synthetic fibres. Every fibre has various properties, and polymer composites reinforced with natural fibre are known to have superior mechanical properties. In this study, the pineapple leaf fibre/polylactic acid (PALF/PLA) composites filaments are developed with several processes, including grinding, sieving, chemical treatment, and hot compression on the composites with various fibre loadings of 1, 3, and 5%, continued with the crushing and the extrusion processes. Then, mechanical testing for specific flexural and tensile testing was conducted on the PALF/PLA filament composites. The findings showed that the PALF/PLA composites with a 5% fibre loading exhibited the highest mechanical properties in both flexural and tensile properties. In conclusion, 5% fibre loading of PALF/PLA composites filaments can be used as an alternative material to replace pure PLA.